2019
DOI: 10.1371/journal.pone.0217994
|View full text |Cite
|
Sign up to set email alerts
|

Fast optimization of non-negative matrix tri-factorization

Abstract: Non-negative matrix tri-factorization (NMTF) is a popular technique for learning low-dimensional feature representation of relational data. Currently, NMTF learns a representation of a dataset through an optimization procedure that typically uses multiplicative update rules. This procedure has had limited success, and its failure cases have not been well understood. We here perform an empirical study involving six large datasets comparing multiplicative update rules with three alternative optimization methods,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 47 publications
(61 reference statements)
0
4
0
Order By: Relevance
“…, where L i−1 and L i are respectively the values of the loss function after the last and the previous iterations [13].…”
Section: Methodsmentioning
confidence: 99%
“…, where L i−1 and L i are respectively the values of the loss function after the last and the previous iterations [13].…”
Section: Methodsmentioning
confidence: 99%
“…However, our as shown in the previous experiments, our method performs better. Most of this time complexity is due to the multiplicative update rule used in NMF-based algorithms and can be reduced using alternative approaches as discussed in [67]. Lazega Law Firm [68] is a multiplex social network with 71 nodes and three layers representing Co-work, Friendship and Advice relationships between partners and associates of a corporate law firm.…”
Section: ) Scalabilty Analysismentioning
confidence: 99%
“…In [54] the authors compared different approaches for solving the NMTF problem on six large data-sets. Comparing alternating least squares, projected gradients, and coordinate descent methods they concluded that methods based on projected gradients and coordinate descent converge up to twenty-four times faster than multiplicative update rules and coordinate descent-based NMTF converges up to sixteen times faster compared to well-established methods.…”
Section: Related Workmentioning
confidence: 99%